Pemanfaatan Media Digital dalam Bina Pribadi Islam: Upaya Penguatan Karakter Islami Siswa SMPIT Al-Manar Pangkalan Bun Kotawaringin Barat - Ulum, M. Misbahul Ulumudin; Nadia Arifatul Khoiri Fauzi; Isnani Zakiyah (Kaffah: Jurnal Pendidikan dan Sosio Keagamaan, 2025)
This study aims to investigate how digital media builds Islamic character of students at SMPIT Al-Manar Pangkalan Bun. This is based on the fact that young people often use digital media without being guided by Islamic values. Metode yang digunakan adalah kualitatif dengan pendekatan case study. Observations, interviews, and documentation were used to collect data. Hasil menunjukkan bahwa guru telah mendukung aktivitas Bina Pribadi Islam (Islamic Personal Development) dengan menggunakan digital media, seperti video pengajaran Islam, konten Islamic di YouTube, dan aplikasi pembelajaran Qur'an. Reading the Qur’an, praying on time, and polite behavior improved as a result of digital media helping students build their Islamic character. However, issues such as excessive use and lack of supervision of media remain. This study finds that digital media can be useful for teaching Islamic character to students if used properly and with control. Keywords: digital media, Islamic character, Islamic personal development, SMPIT, religious education